Pemerintahan dan Gender : Studi Tentang Peran Perempuan Dalam Penyelenggaraan Pemerintahan - Vira Nurul Fitriyani (Peneliti.net, 2022)
The problem of gender is an issue that demands social and cultural construction justice between men and women. World Bank data (2019) notes that the participation of Indonesian women in women's representation in parliament is still weak, ranking 7th in Southeast Asia. Support in efforts to increase women's participation in the government sector is an effort in terms of government decision making that is more accommodating and substantial. Through the affirmation action that places a quota of The results of this study indicate that the participation and role of Indonesian women in the realm of government has increased positively from time to time. It is undeniable that Indonesian women have a role in development in the political field, whether they are involved in parties, the legislature, or in government as decision makers who are pro to women and children.